Gestión de ingresos y ejecución de gastos de la APAFA en la IEP San Suan Bautista de la Salle, periodo 2022 - Hidalgo Ramirez, Milagros de Maria (2023)
The objective of the research was to determine the relationship between the management of income and the execution of expenses of the APAFA in the Secondary Educational Institution for Minors San Juan Bautista de la Salle, period 2022, since I chose to be a descriptive study - correlational and low a non-experimental design, was made up of a sample of 181 parents, those who applied the survey technique and the questionnaire as an instrument for data collection. After the results, it was determined that the admission management in said institution has been carried out on a regular basis, this is due to the fact that the ordinary fees are rarely established by consensus of all the associated parents, in addition, the board of directors rarely develops concessions of kiosks or similar activities to obtain a fixed income and that the parents argue that the APAFA never uses bank accounts that contribute to managing money; on the other hand, the execution of expenses is classified as regular, because the money is sometimes used for the development of training programs aimed at parents; as well as the board of directors sometimes makes the economic report of each activity carried out. Finally, it was determined that there is a significant relationship between income management and execution of APAFA expenses in the IEP San Juan Bautista de la Salle-2022, which has been corroborated by a coefficient of 0.692 (average positive) and a next. of 0,000 Keywords: Income management, expense execution